2017
DOI: 10.2217/nnm-2017-0022
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nanoparticle Size on the Ability to Cross the Blood–Brain Barrier: An In Vivo Study

Abstract: These findings promote the optimization of nanovehicles for transport of drugs through the BBB. The insulin coating of the particles enabled targeting of specific brain regions, suggesting the potential use of INS-GNPs for delivery of various treatments for brain-related disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
142
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 237 publications
(157 citation statements)
references
References 52 publications
5
142
0
1
Order By: Relevance
“…These transport data are in qualitative agreement with transport of silica nanoparticles through a static coculture rat BBB model, which showed that 100 nm spherical particles crossed more than 400 nm spherical particles, although transport for intermediate sizes was not reported . Literature data on the dependence of nanoparticle accumulation in the brain in vivo do not have sufficient granularity to quantitatively distinguish between endothelial accumulation and transport into the parenchyma . Further, these in vivo nanoparticle accumulation data are confounded by size‐dependent persistence of nanoparticles in the blood.…”
Section: Resultssupporting
confidence: 64%
“…These transport data are in qualitative agreement with transport of silica nanoparticles through a static coculture rat BBB model, which showed that 100 nm spherical particles crossed more than 400 nm spherical particles, although transport for intermediate sizes was not reported . Literature data on the dependence of nanoparticle accumulation in the brain in vivo do not have sufficient granularity to quantitatively distinguish between endothelial accumulation and transport into the parenchyma . Further, these in vivo nanoparticle accumulation data are confounded by size‐dependent persistence of nanoparticles in the blood.…”
Section: Resultssupporting
confidence: 64%
“…The optimal size of a NP also depends on the specific location and type of targeted tissue [70], for example, most tumors have a vascular pore cutoff size between 380 and 780 nm [71]. However, Kang et al have shown that for a gold NP has to be around 10 to 20 nm in diameter to effectively cross the BBB, while particles around 50 and 100 nm diameter were not distributed well enough into the brain [72,73]. nanospheres and nanorods [110].…”
Section: Nanocarriers Nanoparticles and Vectorsmentioning
confidence: 99%
“…Ultrafine particles are expected to be deposited in the deepest part of the respiratory tract (Chow and Watson 2007;Hinds 1999). The smallest nanoparticles (<50 nm) can even cross the blood-brain barrier (Betzer et al 2017;Oberdorster et al 2004). To compare the potential health impact of ultrafine particles measured for hookah and cigarette mainstream smoke inhaled into the respiratory tract, the particle concentration for different size ranges was determined.…”
Section: Size Distribution Of Particles In Mainstream Smokementioning
confidence: 99%